keberkesanan program bandar selamat dari persepsi penduduk kajian kes: bandaraya Shah Alam - Zainudin, Ainur Zaireen; Abdul Malek, Jalaluddin (Penerbit UTM Press, 2010)
Abstract. In recent years, safety becomes one of prominent issues amongst urban community. This issue has led to the implementation of Safe City Programme in Malaysia as to strengthening the urban community safety. In Malaysia, Shah Alam City has been declared as the first Safe City in this country. However, this recognition is arguable due to its crime rates, which is found higher compared with other cities. In fact, crime rates appear to be common indicator among the urban community for measuring the urban safety. Therefore, a case study has been carried out in Shah Alam residential area as to have better understanding about the concept of Safe City Programme and its effectiveness towards community safety. The evaluation is based on the community perception in which, gathered from indepth interview. It is found that the respective local authority is highly relied on the physical environment that is believed to be effective in preventing crime. On the other hand, the physical factor has brought less effect to the community, but they have come up with their own safety strategies through numerous social activities as to combat crime at their place.